Root Adaptive Responses to Aluminum-Treatment Revealed by RNA-Seq in Two Citrus Species With Different Aluminum-Tolerance - Guo, Peng; Qi, Yi-Ping; Yang, Lin-Tong; Lai, Ning-Wei; Ye, Xin; Yang, Yi; Chen, Li-Song (Frontiers in Plant Science, 2017)
Seedlings of aluminum (Al)-tolerant Citrus sinensis and Al-intolerant Citrus grandis were fertigated daily with nutrient solution containing 0 and 1.0 mM AlCl3•6H2O for 18 weeks. The Al-induced decreases of biomass and root total soluble proteins only occurred in C. grandis, demonstrating that C. sinensis had higher Al-tolerance than C. grandis. Under Al-treatment, C. sinensis roots secreted more citrate and malate than C. grandis ones; less Al was accumulated in C. sinenis than in C. grandis leaves. The Al-induced reduction of phosphorus was lesser in C. sinensis roots and leaves than in C. grandis ones, whereas the Al-induced increase of sulfur was greater in C. sinensis roots and leaves. Using RNA-seq, we isolated 1905 and 2670 differentially expressed genes (DEGs) from Al-treated C. sinensis than C. grandis roots, respectively. Among these DEGs, only 649 DEGs were shared by the two species. Further analysis suggested that the following several aspects conferred C. sinensis higher Al-tolerance: (a) Al-treated C. sinensis seedlings had a higher external Al detoxification capacity via enhanced Al-induced secretion of organic acid anions, a higher antioxidant capacity and a more efficient chelation system in roots; (b) Al-treated C. sinensis seedlings displayed a higher level of sulfur in roots and leaves possibly due to increased uptake and decreased export of sulfur and a higher capacity to maintain the cellular phosphorus homeostasis by enhancing phosphorus acquisition and utilization ; (c) Cell wall and cytoskeleton metabolism, energy and carbohydrate metabolism and signal transduction displayed higher adaptative responses to Al in C. sinensis than in C. grandis roots; (d) More upregulated than downregulated genes related to fatty acid and amino acid metabolisms were isolated from Al-treated C. sinensis roots, but the reverse was the case for Al-treated C. grandis roots. These results provide a platform for further investigating the roles of genes possibly responsible for citrus Al-tolerance.